Collection calendar: the diversity and local knowledge of wild edible plants used by Chenthang Sherpa people to treat seasonal food shortages in Tibet, China - Xiao-Yong Ding; Yu Zhang; Lu Wang; Hui-Fu Zhuang; Wen-Yun Chen; Yu-Hua Wang (BMC, 2021)
Abstract Background Wild edible plants (WEPs) are non-cultivated and non-domesticated plants used for food. WEPs provided food, nutrition, herbs and other plant products for people in underdeveloped areas, such as the Everest region, to maintain their daily lives. Chenthang Town is the only Sherpa ethnic township in Tibet, China. The core purpose of this research is to investigate, collect and record the WEPs and related local knowledge and functions within the Sherpa community. The ultimate goal is to answer the question of why Sherpa people choose these particular plants. Materials and methods The field study was carried out in the six Sherpa communities of Chenthang Township from September 2019 to August 2020. The WEPs and related local knowledge were collected through semistructured interviews and direct observations. The field work was performed with the assistance of local guides. During the field survey, we collected plant specimens based on the principle of one plant with one vernacular name. In this study, we utilised a use report (UR) and cultural importance index (CI) to evaluate the comprehensive utilization value of WEPs in the daily diet of Sherpa people. Results We interviewed 78 people individually who provided us with 1199 use reports. In total, we collected 84 WEPs belonging to 65 genera in 41 families. These species were identified as 78 distinct ethno-species by local people, and the vernacular name of each ethno-species was recorded. Then, these use reports were classified into six use categories. All these plants were native wild plants. In these plants, Arisaema utile, Sorbus cuspidata and Elaeagnus umbellata have been introduced into home gardens by local people. Following the description of the Sherpa people, we articulated a collection calendar for WEPs. The Sherpa collect WEPs throughout nearly the entire year, January and February being the exceptions. Conclusion The collection calendar of wild edible plants reflects the wisdom of the Sherpa in terms of survival. The Sherpa cleverly survive the food shortage periods by harnessing the phenology of different species. In general, WEPs can provide the Sherpa with seasonal carbohydrates, nutrition, healthcare supplements and other products and services necessary for survival, which is likely why the Sherpa choose these plants.